Sanitary aspects and technological challenges of whole milk microfiltration at low temperatures - Fagnani, Rafael; Mexia, Marisa Marroni; Puppio, Ana Amélia Nunes; Battaglini, Ana Paula Pavão (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effects of whole milk microfiltration at low temperatures on bacterial counts and on its shelf life. The microfiltration process was evaluated at two temperatures (30 and 50ºC) and compared with the slow pasteurization process. Both slow pasteurization and microfiltration reduced the initial counts of aerobic mesophilic and psychrotrophic bacteria, as well as total coliforms in whole milk. Microfiltration at 50ºC was as effective as the pasteurization process, since it reduced the initial count of aerobic mesophilic bacteria in 4.4 log cycles; increased the product’s shelf life, which reached 30 days without exceeding 1,000 CFU mL‑1; and eliminated coliform counts at the temperatures of 35 and 45ºC, established by the Brazilian legislation. Microfiltration at 30°C reduced the aerobic mesophilic bacteria counts by 2.2 log cycles; however, Escherichia coli was found in the product, which exhibited a shelf life of less than five days. Therefore, microfiltration at 30ºC can be associated with thermal treatments, but, when applied alone, it shows unsatisfactory results.